Optimization of Traffic Education in Kamsel Unit for Prevention of Traffic Accidents Among Students in the Jurisdiction of Kendal Police Resort - Barus, Eginta (Advances in Police Science Research Journal, 2024)
In conducting research on the Kendal Police Traffic Unit (Satlantas Polres Kendal), the author found several facts that the number of traffic accidents among students has increased. This has led the author to address this issue through police activities in the form of traffic community development and traffic education. This task and function at the level of the Kendal Police Resort is carried out by the Kamsel Unit of the Satlantas Kendal Police Resort. The increasing number of traffic accidents in Kendal indicates that dikmas activities have not had a major impact on students. This is because Kendal is on the Pantura route, so the volume of heavy vehicles is a real threat to students and there are many other motorcycle users whose driving speed limits are quite high. So more vigilance is needed to be able to drive in Kendal. So an analysis was carried out on the implementation of dikmas lantas to students and what the impact was. Then the right steps can be taken to students. The steps that must be implemented are the need for appropriate methods and strategies and tactics for students because this is a group that is categorized as special. So there must be a difference between the form of activities, the way of delivery, and other factors that influence when the community service is carried out. Therefore, 5 (five) guidelines are applied for each dikmas lantas, 8 (eight) forms of activities and IBQ (Influence Behaviour Questantionare) strategies and tactics. The purpose of implementing guidelines and forms of activities is to design steps to strengthen weaknesses and be able to manage opportunities as well as reduce risks to students in Kendal.